Souvenirs as Cultural Symbols: A Case Study of Panda Symbolism and the Chinese Knot from China - Dian Sari Unga Waru; Mustarih, Nirdayanti; Andi Faisal (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study explores the role of souvenirs as cultural symbols, focusing on two iconic representations from China: the panda and the Chinese knot. In the context of global tourism, souvenirs serve not only as mementos but also as representations of a nation's identity and cultural values. The study applies Charles Sanders Peirce’s semiotic theory to analyze two iconic Chinese souvenirs: the panda and the Chinese knot. Using qualitative textual analysis, it explores how these symbols function within the triadic semiotic framework—representamen (the physical form), object (the cultural meaning), and interpretant (the perceived interpretation). The key findings highlight that the panda, as a national symbol, not only embodies China’s identity and commitment to conservation but also serves as a tool of cultural diplomacy, promoting a peaceful image globally. Meanwhile, the Chinese knot reflects Confucian values such as harmony, good fortune, and eternity, while also showcasing the aesthetic and philosophical aspects of traditional Chinese craftsmanship. This study demonstrates that souvenirs act as powerful media of cultural communication and play a role in shaping global perceptions and strengthening a nation's identity. Therefore, souvenirs should be studied not only from economic and tourism perspectives but also through cultural and semiotic lenses.